Disclosure Principle as Ex-Ante Rules for Combating Big Tech’s Abuse of Dominance in Digital Market: A Comparative Analysis - Rakhmawati, Catur Septiana (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
This study discusses the weaknesses of Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition in handling the abuse of dominance by big tech in the digital market. This study also explores lessons from how the European Union (EU) and Japan implement the disclosure principle to prevent such abuse. This normative study employs statutory, conceptual, and comparative approaches. The findings are as follows: first, Law Number 5 of 1999 does not implement ex-ante measures such as the “disclosure principle,” and prevention efforts are practically non-existent, particularly in handling dominance abuse. Second, a comparative study of the EU and Japan found that the EU has enacted the Digital Markets Act (DMA), which comprehensively regulates the abuse of dominance by big tech companies and categorizes them as gatekeepers. The DMA establishes the gatekeeper threshold and includes the duty to notify the European Commission voluntarily under Articles 5, 6, and 7 of the DMA. Japan has the Act on Improving Transparency and Fairness of Digital Platforms 2021, an ex-ante regulation that implements the disclosure principles on digital platforms. Based on these two comparisons, the main idea of such regulations is to implement the disclosure principle as an ex-ante rule for business actors who meet the threshold and to burden them with certain obligations. This approach allows authorities to perform supervision and prevent abuse of dominance by big tech optimally.